Population, consumption and climate colonialism - Patrick Hassan (The Journal of Population and Sustainability)
Strategies for combatting climate change that advocate for human population limitation have recently been understandably criticised on the grounds that they embody a form of ‘climate colonialism’: a moral wrong that involves disproportionately shifting the burdens of climate change onto developing nations (which have low per capita emissions but high fertility rates) in order to offset burdens in affluent nations (which have high per capita emissions but low fertility rates). This article argues that once the relevance of population growth to climate change has been correctly understood as working in tandem with consumption levels, this objection fails as a general criticism. Moreover, even if population could be ignored as a variable, the climate colonialism charge would re-emerge in a different form, since, at present population sizes, it would be environmentally catastrophic for developing nations to reach the production ambitions which see their per capita emissions massively increase. Even if emission reductions in affluent nations are (rightly) prioritised, there are good reasons to prevent enormous growth of emissions in developing countries. Those environmental risks become much greater given developing nations’ projected population increases in the coming century. The article then explores how the necessary radical environmental policies pertaining to fertility rates might be enacted in non-coercive ways, reducing the sting of the ‘climate colonialism’ charge. The article ends by considering some reasons to be moderately sceptical about such policies.